THE EFFECT OF AGE IN ENGLISH LANGUAGE TEACHING: IS IT TRUE? - Herwiana, Sakhi (Jurnal Bahasa Lingua Scientia, 2017)
It is believed that age become the important factorÂ  to language acquisition. Learners with the age under the puberty or in the critical period can learn the language faster than adult. However, this case is not completely true. I have an opinion that learning the language in the younger age does not guarantee that they can succeed to be language learners. Many facts and researches found thatÂ  the older is better in learning the language. This could be another factor affectingÂ  the language acquisition. Motivation is the most important key to acquire the language. It does not matter whether they learn in younger age or in older age. As long as they have motivation to learn, they will be successfull in acquiring the language. Therefore, English teachers have to create an effective and innovative in teaching and learning process in order to enhance the learnersâ motivation.